Hyponatremia and extrapontine myelinolysis in a patient with COVID‐19: A case report - Muhammad Abd Ur Rehman (14777608) (2023)
Until we have strong evidence to the contrary, symptomatic hyponatremia should be treated with extra caution in COVID-19 co-infection patients as the latter could be another risk factor for the development of extrapontine myelinolysis. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4463